Pengaruh sosialisasi tentang keamanan pangan terhadap skor keamanan pangan pada warung bubur kacang hijau (BURJO) di Tembalang Semarang - Setya Budi Muhammad Abduh; Bagaskara Irvan; Sri Mulyani; Yoyok Budi Pramono; Nurwantoro Nurwantoro; Rafli Zulfa Kamil (Jurnal SAGO Gizi dan Kesehatan, 2024)
AbstractBackground: Food safety is an important factor in maintaining human health. The more aware people are of food safety, foodborne diseases or diseases transmitted through food can be suppressed. The number of Burjo stall users is not yet known whether it is accompanied by awareness about food safety. One of the keys to food safety is maintaining hygiene and sanitation, so it is necessary to socialize food safety in Burjo stalls.Objective: To assess the impact of food safety campaigns on Burjo stalls in the Tembalang area of Semarang, as evaluated by food safety scores and total microbial counts.Method: Surveys, observations, and interviews were conducted at 5 Burjo stalls to obtain data on food safety scores (FSS). Samples of fried tempeh were also collected to test for microbial contamination using the total plate count method at the Food Microbiology Laboratory, Faculty of Animal Husbandry and Agriculture, Diponegoro University, Semarang. The entire study spanned three months, from June  to August 2023. Following the initial survey, food safety campaigns were conducted twice on the 2nd and 15th days, accompanied by the provision of personal protective equipment for food handlers. Subsequently, a follow-up survey was conducted to gather comparative food safety data.Results: The food safety score before and after food safety socialization was 0,862 and 0,939, while the microbial contamination (CFU/g) was 2,18x104 and 1,31x104. Food safety score increased by 8,96% while microbial contamination increased by 112,41% but still within the safe consumption threshold.Conclusion: Food safety socialization accompanied by the provision of simple personal protective equipment for food handlers in Burjo stalls is effective in improving food safety status and the category of safe consumption.